Intestinal loads of extended-spectrum beta-lactamase and Carbapenemase genes in critically ill pediatric patients - Dahdouh, Elias; Cendejas-Bueno, Emilio; Ruiz-Carrascoso, Guillermo; Schüffelmann, Cristina; Lázaro-Perona, Fernando; Castro-Martínez, Mercedes; Moreno-Ramos, Francisco; Escosa-García, Luis; Alguacil-Guillén, Marina; Mingorance, Jesús (Frontiers in Cellular and Infection Microbiology, 2023)
Intestinal colonization by Multi-Drug Resistant Organisms (MDROs) can pose a threat on the health of critically ill patients. The extent of colonization by these organisms is related to previous antibiotic treatments and their ability to cause infections among adult patients. The aim of this study is to determine the relationship between the intestinal Relative Loads (RLs) of selected antibiotic resistance genes, antibiotic consumption and extra-intestinal spread among critically ill pediatric patients. RLs of blaCTX-M-1-Family, blaOXA-1, blaOXA-48 and blaVIM were determined in 382 rectal swabs obtained from 90 pediatric critically ill patients using qPCRs. The RLs were compared to the patients’ demographics, antibiotic consumption, and detection of MDROs from extra-intestinal sites. 16SrDNA metagenomic sequencing was performed for 40 samples and clonality analyses were done for representative isolates. 76 (74.45%) patients from which 340 (89.01%) rectal swabs were collected had at least one swab that was positive for one of the tested genes. Routine cultures did not identify carbapenemases in 32 (45.1%) and 78 (58.2%) swabs that were positive by PCR for blaOXA-48 and blaVIM, respectively. RLs of above 6.5% were associated with extra-intestinal spread of blaOXA-48-harboring MDROs. Consumption of carbapenems, non-carbapenem β-lactams, and glycopeptides were statistically associated with testing negative for blaCTX-M-1-Family and blaOXA-1 while the consumption of trimethoprim/sulfamethoxazole and aminoglycosides was associated with testing negative for blaOXA-48 (P<0.05). In conclusion, targeted qPCRs can be used to determine the extent of intestinal dominance by antibiotic resistant opportunistic pathogens and their potential to cause extra-intestinal infections among a critically ill pediatric population.